KEPEMIMPINAN KEPALA MADRASAH DALAM PERSPEKTIF MANAJEMEN BERBASIS SEKOLAH SEBAGAI AKSES PENDIDIKAN BERKUALITAS DI ERA INDUSTRI REVOLUSI 4.0 - Achmad Syakur; Sigit Tri Utomo (Journal of Research and Thought on Islamic Education (JRTIE), 2021)
Education in the era of the industrial revolution 4.0 should form people who are dedicated to the system, but the education system in several educational institutions in reality there is still an opportunity for someone to take actions that are not in accordance with the regulations made by the educational institution such as professional and quality institutional management. , thus providing the impact of changes in an educational process system. This quality education process, it has implications for the direction and progress of an educational institution. This is where the role of a madrasa principal plays an important role. The data collection method in this study uses library research. In this case, it is a variant of qualitative research, data collection can use observational interviews and documentation. At this stage, the researcher tries to select data (books) that have relevance to the leadership of the madrasah principal in the perspective of MBS as access to quality education in the era of the industrial revolution 4.0. In this paper, in analyzing this paper with a hermeneutic approach, the author describes behind the text there is a context meaning or behind the explicit meaning, there is an explicit meaning if interpreted literally it can be interpreted as interpretation or interpretation. This method step is intended to capture the meaning, values and intentions of the madrasa principal's leadership in the MBS perspective as access to quality education in the era of the industrial revolution 4.0. Then the author also uses synthetic analysis which means the stages of an object of scientific study that link an articulation of one meaning with another meaning which is then found a knowledge with a new articulation in the form of the leadership of the head of the madrasah in the perspective of MBS as access to quality education in the era of the industrial revolution 4.0. Keywords: Leadership of Madrasah Principals, SBM Perspective, Quality Education, Industrial Era 4.